2014
DOI: 10.1057/jibs.2014.31
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the broader agency perspective for studying headquarters–subsidiary relations in multinational companies

Abstract: The nature of global business today increases the complexity of multinational companies and highlights the challenges of managing headquarters-subsidiary (HQ-Sub) relationships. We identify key unresolved issues in HQ-Sub relations including closing the gap between headquarters' expectations and subsidiary performance, managing the nested hierarchical relationships across multiple organizational layers, and aligning these relationships across diverse subunits embedded in different social contexts. We propose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
150
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(159 citation statements)
references
References 66 publications
2
150
0
Order By: Relevance
“…Specifically, there is a need to better understand how the CHQ deals with a complex portfolio of heterogeneous business and international units, for example, accounting for bi-directional relationships and considering several organizational layers, such as RHQs and DHQs (e.g., Alfoldi et al, 2012;Mahnke et al, 2012). Research into these CHQ challenges may build on recent advances and applications of suitable theories, such as agency theory (e.g., Hoenen & Kostova, 2014) and network theory (e.g., Vahlne et al, 2012) to account for the multidimensional nature and complexities of these relationships. Further, while particularly research on the multibusiness firm's CHQ has often relied on the assumption that the CHQ has a positive influence on the operating units, there is a need to further examine the potentially harmful role of the CHQ, as recent studies suggest (e.g., Walter et al, 2014).…”
Section: The Chq's Relationsmentioning
confidence: 99%
“…Specifically, there is a need to better understand how the CHQ deals with a complex portfolio of heterogeneous business and international units, for example, accounting for bi-directional relationships and considering several organizational layers, such as RHQs and DHQs (e.g., Alfoldi et al, 2012;Mahnke et al, 2012). Research into these CHQ challenges may build on recent advances and applications of suitable theories, such as agency theory (e.g., Hoenen & Kostova, 2014) and network theory (e.g., Vahlne et al, 2012) to account for the multidimensional nature and complexities of these relationships. Further, while particularly research on the multibusiness firm's CHQ has often relied on the assumption that the CHQ has a positive influence on the operating units, there is a need to further examine the potentially harmful role of the CHQ, as recent studies suggest (e.g., Walter et al, 2014).…”
Section: The Chq's Relationsmentioning
confidence: 99%
“…Our study shows that dual headquarters involvement is a common phenomenon, and although it is particularly relevant for MNCs, it has received little attention from international management scholars. Recently, a few have conceptually addressed the problems that can be associated with dual agency of corporate and divisional or regional headquarters (see Ambos and Mahnke 2010;Hoenen and Kostova 2015). We encourage international management scholars to pursue in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…This issue is particularly visible in the literature on subsidiaries of MNCs where individual subsidiaries are usually conceptualized as units dealing with only one single headquarters which could be the corporate or divisional headquarters. Put differently, current research largely disregards nested headquarters structures within large firms and the fact that subsidiaries might experience involvement in its activities by more than just one headquarters unit (Hoenen and Kostova 2015). Such multiple interaction patterns between one subsidiary and several types of headquarters would reflect complex parenting situations which are covered in extant literature only to a very limited extent (see Goold and Campbell 2002).…”
Section: Parenting In the Multibusiness Firmmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, relationships between HQs and foreign subsidiaries have been referred to as among the most crucial issues in MNE management (Hoenen and Kostova, 2014). Previous studies have also indicated that the longterm prosperity of an organization is linked to the sharing of intangible assets like knowledge (e.g.…”
Section: Introductionmentioning
confidence: 99%